2010
DOI: 10.1002/path.2725
|View full text |Cite
|
Sign up to set email alerts
|

Global DNA methylation in fetal human germ cells and germ cell tumours: association with differentiation and cisplatin resistance

Abstract: Differences in the global methylation pattern, ie hyper- as well as hypo-methylation, are observed in cancers including germ cell tumours (GCTs). Related to their precursor cells, GCT methylation status differs according to histology. We investigated the methylation pattern of normal fetal, infantile, and adult germ cells (n = 103) and GCTs (n = 251) by immunohistochemical staining for 5-(m)cytidine. The global methylation pattern of male germ cells changes from hypomethylation to hypermethylation, whereas fem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
169
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(198 citation statements)
references
References 34 publications
28
169
0
1
Order By: Relevance
“…1A. The concentration from the N.C. cells in this study was similar with the IC50 of CDDP for 72 h in TCam-2 cells reported by Wermann H et al 22 It was reported that PI3K signaling plays a critical role in the occurrence and development of seminoma. 15 Interestingly, we found that LY294002, a PI3K signaling inhibitor, re-sensitized TCam-2 cells with TDRG1 overexpression to CDDP, while IGF-1, a PI3K activator, reversed the positive effect of TDRG1 knockdown on the chemosensitivity of TCam-2 cells to CDDP (Fig.…”
Section: Tdrg1 Regulates Cell Viability During Cddp Treatment In Tcamsupporting
confidence: 72%
“…1A. The concentration from the N.C. cells in this study was similar with the IC50 of CDDP for 72 h in TCam-2 cells reported by Wermann H et al 22 It was reported that PI3K signaling plays a critical role in the occurrence and development of seminoma. 15 Interestingly, we found that LY294002, a PI3K signaling inhibitor, re-sensitized TCam-2 cells with TDRG1 overexpression to CDDP, while IGF-1, a PI3K activator, reversed the positive effect of TDRG1 knockdown on the chemosensitivity of TCam-2 cells to CDDP (Fig.…”
Section: Tdrg1 Regulates Cell Viability During Cddp Treatment In Tcamsupporting
confidence: 72%
“…It has been shown that global methylation status of GCC subtypes differ according to the time point of their developmental arrest; more differentiated cells showed a higher degree of methylation (Okamoto and Kawakami, 2007, Smiraglia et al, 2002, Wermann et al, 2010. It is also known that CIS/GB cells show very little DNA methylation (Netto et al, 2008, Smiraglia et al, 2002, Wermann et al, 2010.…”
Section: Origin Of Gcc and Link To Methylationmentioning
confidence: 99%
“…Subsequent analysis of CpG island methylation showed that there were different methylation profiles in the treated and non-treated cells. For example, the promoter region of the CFLAR (c-FLIP) gene was hypermethylated in the treated cell line (Wermann et al, 2010). CFLAR has an important role in regulation of apoptosis via the caspase pathway and therefore could be a therapeutic target (Yang, 2008), something that needs further evaluation.…”
Section: Cisplatin Sensitivity Of Germ Cell Cancersmentioning
confidence: 99%
See 1 more Smart Citation
“…This conclusion is based on studies using both candidate gene approaches (Koul et al 2002, Smith-Sorensen et al 2002, Honorio et al 2003, Kempkensteffen et al 2006, Lind et al 2006, Brait et al 2012) and genome-wide approaches (Smiraglia et al 2002, Netto et al 2008, Wermann et al 2010, which have mainly focused on adult testicular GCTs (Table 2). Although some of these studies focused on a limited number of genes, microarray and genome-wide studies confirm that the methylation profile distinction between seminomas and non-seminomas is not restricted to just a few specific gene promoters (Lind et al 2007).…”
Section: Dna Methylation In Gctsmentioning
confidence: 99%